Pengaruh ROA dan BOPO terhadap Financial Sustainability Ratio (FSR) di PT BPR Bank Sleman (Perseroda) - Apriliyanto, Anggun; Putra Prasetya, Bangun (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
The growing banking sector has made banks an important part of the country's economy today. PT BPR Bank Sleman (Perseroda) is one of the BUMDs in Sleman Regency which was established to improve the welfare of the community through the financial sector. So that financial sustainability is an important thing related to the sustainability of PT BPR Bank Sleman (Perseroda) in its financial aspects. This study uses independent variables, namely Return on Asset (ROA), Operating Costs of Operating Income (BOPO) with the dependent variable Financial Sustainability. The purpose of this study is to see the effect of Return on Asset (ROA), Operating Cost of Operating Income (BOPO) on Financial Sustainability. This study uses the research object PT BPR Bank Sleman (Perseroda) which has a mission to realize community welfare in the financial sector. Based on the results of the t test on the ROA variable, it has a t count of 0.072. Indicates that the ROA variable has a negative and insignificant effect on the Financial Sustainability Ratio (FSR). While the BOPO variable has a t value of 0.072. indicates that the BOPO variable has a negative and insignificant effect on the Financial Sustainability Ratio (FSR). The results obtained from the F test were calculated at 0.006. This shows that there is a joint influence between Return On Asset (ROA) and BOPO on the Financial Sustainability Ratio (FSR) at PT BPR Bank Sleman (Persero).